(NiSKUSSTWA sOWETSKOGO uZBEKISTANA(B.s 1917-1972 ((NmOSKWAs (NsOWETSKIJ HUDOVNIK(B.s, 1976)
(NiSKUSSTWO sOWETSKOGO uZBEKISTANA PRINALEVIT NARODU E]E K NA^ALU NA[EGO WEKA NE ZNAW[EMU ^TO TAKOE HUDOVESTWENNAQ WYSTAWKA ILI KNIGA OB IZOBRAZITELXNOM ISKUSSTWE(B.s
Keywords: (NISKUSSTWAs